Dracula and Nineteenth Century Anxieties: reverse-colonization, homosexuality, female sexuality and madness - Bodevan, Erica (Revista Espacialidades, 2020)
In Bram Stoker’s Dracula (1897), the vampire seduces his victims in a way they feel they are being willingly corrupted, and thus they believe to be transgressing a number of codes established by the society they are inserted in, such as moral and religious values. This famous vampire has the ability to embody nineteenth-century anxieties, such as the fears of reverse-colonization or immigration, homosexuality, overt female sexuality and psychological disorders, thus defeating the monster means to restore what it is considered to be the rightful social order.